2005
DOI: 10.1002/ar.a.20158
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of connexin43 alters the mutant phenotype of midgestational wnt1 null mice resulting in recovery of the midbrain and cerebellum

Abstract: The midbrain-hindbrain (MHB) junction plays a key role in the patterning of the embryonic neural tube and the formation of brain structures such as the cerebellum. The mitogen wnt-1 is critical for cerebellar development, as evidenced by the lack of MHB region and cerebellar formation in the wnt-1 null embryo. We have generated wnt-1 null embryos overexpressing the gap junction gene connexin43 by crossing wnt-1 null heterozygotes into the CMV43 mouse line. We have confirmed that these mice show an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
(80 reference statements)
2
7
0
1
Order By: Relevance
“…The chick/quail grafting study of Marin and Puelles [56] suggested that the auricle of the chick cerebellum (equivalent to the flocculonodular node of mammals) arises from cells in r2 boundary, but in the absence of confirmatory data in mammals this suggestion must be considered speculative. The intense X-gal staining in the cerebellum is consistent with studies showing that Wnt1 is critical for cerebellar development [57].…”
Section: Prenatal Expression Of Wnt1 In the Central Nervous Systemsupporting
confidence: 88%
“…The chick/quail grafting study of Marin and Puelles [56] suggested that the auricle of the chick cerebellum (equivalent to the flocculonodular node of mammals) arises from cells in r2 boundary, but in the absence of confirmatory data in mammals this suggestion must be considered speculative. The intense X-gal staining in the cerebellum is consistent with studies showing that Wnt1 is critical for cerebellar development [57].…”
Section: Prenatal Expression Of Wnt1 In the Central Nervous Systemsupporting
confidence: 88%
“…These effects were blocked by the nitric oxide (NO) inhibitor l -NG-nitroarginine methyl ester ( l -NAME), suggesting that NO may play a role in this mechanism. In addition, cerebellar formation defects found in Wnt-1 knockout mice are reversed by Cx43 overexpression [106]. These findings are consistent with earlier work, showing that Cx43 is a functional target of Wnt signaling in the brain [107].…”
Section: Sclerostin/wnt/β-cateninsupporting
confidence: 91%
“…In support of this hypothesis, we have found major sex dependent differences in gene expression changes in heart ventricles and atria (Iacobas et al, 2010), and it was reported that transgenic deletion of the astrocyte-specific gap junction gene Gja1 (encoding Cx43) in a GFAP-targeted strategy led to markedly different morphological and behavioral phenotypes in two different mouse strains (Wiencken-Barger et al, 2007). Moreover, these results were reminiscent of the profound destruction of the midbrain-hindbrain region obtained when the mitogen Wnt1 was deleted (Melloy et al, 2005); strikingly, when the authors crossed Wnt-1 heterozygotes into a Cx43 overexpressing mouse line, the expression of anatomically correct cerebellum was rescued in a substantial percentage of offspring (Melloy et al, 2005). Thus, the loss of one signaling molecule can be compensated by overexpression of a gap junction protein.…”
Section: Discussionmentioning
confidence: 96%